Dynamic Characteristics Analysis and Applications of Electromagnetic Environment Based on Group Perception - Peiwei Gao; Yongfeng Zhi; Chufeng Hu (International Journal of Antennas and Propagation)
In collectively perceiving an electromagnetic environment, the discrete or statistical method is used to characterize its characteristics. The information received by the sensor is not correlated with each other; therefore, there is no way to obtain the integral dynamic characteristics of an electromagnetic environment. Based on the statistical manifold and the information geometry theory, this paper takes group perception sensors in an electromagnetic space as an associated whole to measure an electromagnetic field in its space. The probability density function of the field distribution measured at any moment is mapped on to a statistical manifold. The “information distance” between the probability density functions of measurement samples at different moments of the statistical manifold is solved to reveal the changes in the whole electromagnetic environment. Simulations are carried out in assumed electromagnetic environments. The simulation results show that when a target enters the electromagnetic space and as its electromagnetic characteristics and positions change, the distribution of “KLD information distances” of its electromagnetic environment changes as well. The method can perceive the RCS of target with −26 dBsm and connect the target with its position information, indicating that the use of the “KLD information distance” distribution can characterize the integral dynamic characteristics of an electromagnetic environment.